2017
DOI: 10.3389/fmicb.2017.02037
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study of the Sorbicillinoid Gene Cluster in Trichoderma reesei

Abstract: Sorbicillinoids are a diverse group of yellow secondary metabolites that are produced by a range of not closely related ascomycetes, including Penicillium chrysogenum, Acremonium chrysogenum, and Trichoderma reesei. They share a similarity to the name-giving compound sorbicillin, a hexaketide. Previously, a conserved gene cluster containing two polyketide synthases has been identified as the source of sorbicillin, and a model for the biosynthesis of sorbicillin in P. chrysogenum has been proposed. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 29 publications
4
79
0
Order By: Relevance
“…As a well-known industrial strain for the production of cellulases, hemicellulases, and recombinant proteins [ 20 ], T. reesei is also a rich source of secondary metabolites [ 21 , 22 ], a point which often is overlooked. It has been observed that T. reesei forms yellow pigments during growth [ 23 , 24 ], which have been identified as a mixture of sorbicillin, sorbicillinol and sorbicillinoids [ 9 , 25 , 26 ]. More recently, the biosynthesis pathway of sorbicillinoids in P. chrysogenum [ 27 ] and T. reesei [ 25 ] has been proposed, wherein all the related genes are clustered on the genome the same way as most genes involved generally in secondary metabolites production [ 9 , 19 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a well-known industrial strain for the production of cellulases, hemicellulases, and recombinant proteins [ 20 ], T. reesei is also a rich source of secondary metabolites [ 21 , 22 ], a point which often is overlooked. It has been observed that T. reesei forms yellow pigments during growth [ 23 , 24 ], which have been identified as a mixture of sorbicillin, sorbicillinol and sorbicillinoids [ 9 , 25 , 26 ]. More recently, the biosynthesis pathway of sorbicillinoids in P. chrysogenum [ 27 ] and T. reesei [ 25 ] has been proposed, wherein all the related genes are clustered on the genome the same way as most genes involved generally in secondary metabolites production [ 9 , 19 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that T. reesei forms yellow pigments during growth [ 23 , 24 ], which have been identified as a mixture of sorbicillin, sorbicillinol and sorbicillinoids [ 9 , 25 , 26 ]. More recently, the biosynthesis pathway of sorbicillinoids in P. chrysogenum [ 27 ] and T. reesei [ 25 ] has been proposed, wherein all the related genes are clustered on the genome the same way as most genes involved generally in secondary metabolites production [ 9 , 19 , 25 ]. This cluster also contains two transcriptional factors, YPR1 and YRP2, and a transporter [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ap ossible candidate for this step in the atn gene cluster is AtnJ,w hich shows 33 %i dentity to Ops4, af lavin-dependent monooxygenase in oosporein biosynthesis. [18] With compounds 11 a and 11 in hand, we next sought to verify the function of AtnJ in vitro.I ntron-free atnJ was subcloned into pGEX4T-1 and high-level expression was achieved in E. coli. Both 11 and 11 a can be utilized by the atn biosynthetic pathway,s ince feeding of 11 or 11 a to DatnG restored the production of 3 ( Figure S6).…”
mentioning
confidence: 99%
“…In addition to tlx1 and tlx2 , the upregulated geneset includes two putative PKS encoding genes, one putative NRPS encoding gene, one putative hybrid PKS/NRPS encoding gene, and one putative terpenoid synthase encoding gene. Of particular note, two genes (SMF2FGGW_102078 and SMF2FGGW_102079) encoding putative PKSs that are close homologues of SOR1 and SOR2, two PKSs responsible for the synthesis of yellow pigment in T. reesei (Derntl et al, ; Derntl, Rassinger, Srebotnik, Mach, & Mach‐Aigner, ), show dramatic decreased expression in the Δ Tlstp1 strain, which is in accordance with the remarkable reduction of yellow pigment in the culture supernatant of Δ Tlstp1 (Figure S3). In addition to these two genes, another two genes encoding a putative PKS and a putative NRPS with unknown products are also downregulated in the absence of Tl STP1.…”
Section: Resultsmentioning
confidence: 61%